Effect of Biochar on the Production of L-Histidine From Glucose Through Escherichia coli Metabolism - E, Yang; Meng, Jun; Cai, Heqing; Li, Caibin; Liu, Sainan; Sun, Luming; Liu, Yanxiang (Frontiers in Bioengineering and Biotechnology, 2021)
Biochar is a carbon-rich product of the pyrolysis of agricultural waste. Annual agricultural biomass waste provides a large amount of raw material for biochar preparation. There are many reports on biochar-stimulating His production, and genetic engineering is the main traditional method for promoting His production in E. coli. The aim of this study was to show that biochar utilization induces His production. The His concentration in the biochar treatment was significantly higher than that in the control. The most optimal concentration was found to be 3%, and 7% is the lethal dose. E. coli was inhibited in the high-concentration treatment. Docking technology was employed to identify the molecules from biochar interacting with regulatory protein (HisG) in order to understand the mechanism of biochar promoting His production in E. coli. The results indicated that eugenol, salicyl alcohol, and 1,2,3-trimethylcyclopentane could interact with HisG. These three compounds play regulatory roles in His production, and the hisG gene expression fully supports this conclusion.